Depressed autonomic nervous system function in African Americans and individuals of lower social class: a potential mechanism of race- and class-related disparities in health outcomes. - Lampert, Rachel; Ickovics, Jeannette; Horwitz, Ralph; Lee, Forrester (American heart journal, 2005)
Both race and social class influence cardiovascular outcomes, through mechanisms not yet fully understood. Minority race and lower social class are sources of chronic stress, which can alter autonomic nervous system function. Heart rate variability (HRV), a measure of autonomic function, is also an important predictor of cardiovascular outcomes.
Keywords: Adult; African Americans; Autonomic Nervous System; Cardiovascular Diseases; Female; Hispanic Americans; Humans; Male; Middle Aged; Multivariate Analysis; Prospective Studies; Risk Factors; Social Class; Stress, Psychological